Fabrication of micro/nanoparticles of drugs for pharmaceutical applications - Kakran, Mitali (2013)
Many drugs are of very poor water solubility, so they tend to be eliminated from the gastrointestinal tract before they could be absorbed into the blood circulation. This results in low bioavailability and poor dose proportionality, and therefore leads to an overall inefficient treatment for the patients. Modifications to the drug substance itself and the creation of specific formulations have been used to enhance the dissolution rate as well as bioavailability of poorly water soluble drugs. Physical modifications to increase the surface area, solubility and wettability of the drug particles typically focus on particle size reduction and generation of amorphous states.